Colorimetric estimation of vancomycin using modified silver nanoparticles and implementing it on various types of pharmaceutical perpetrations - MOHAMMED AHMED AL-KARAMI; MOHAUMAN MOHAMMAD AL-RUFAIE (Nusantara Bioscience, 2022)
Abstract. Al-Karami MA, Al-Rufaie MM. 2022. Colorimetric estimation of vancomycin using modified silver nanoparticles and implementing it on various types of pharmaceutical perpetrations. Nusantara Bioscience 14: 70-77. The current research proposes a simple, quick, and sensitive method for determining the pure state of vancomycin (Van) and several of its medicinal formulations. The antibiotic (Van) effectively reduces the ore mineral salt from silver nitrate (Ag+) to silver nanoparticles. Polyvinylpyrrolidone was used as a stabilizer in a medium using sodium hydroxide as a base. The highest absorption of the vancomycin oxidation-reduction product occurs at 440 nm. The calibration curve is measured, and the following data is generated, indicating that the Beer-Lambert Law is followed within the concentration range of 2.5-70 parts per million. Sandal's molar absorptivity was 2.0043 x 104 L/mol.cm, and its sensitivity was 0.0723 g/cm2. The correlation coefficient was 0.9987, and the standard deviation rate was 0.402%. The biological influence of several Gram-positive and Gram-negative bacteria was researched, and the efficacy of the samples prepared on these bacteria has shown to be promising.